Aspects that characterize the teaching of Spanish in primary education: A multiple case study - Martínez Cruz, Efrén; Moreno Olivos, Tiburcio (IE Revista de Investigación Educativa de la REDIECH, 2023)
The primary school curriculum with a competency-based approach proposes teachers to teach Spanish by mobilizing knowledge, skills, values, and attitudes when developing instructional projects on different social practices of the language. This article aims to share some features that characterize the teaching of Spanish identified in six teachers, by the use of an ethnographic investigation with a multiple case study, carried out from August 2017 to December 2018. Teachers teach students by explaining the content of the coursebook with the support of gestures, movements, drawings, and diagrams on the board; they ask questions to know what students have learned about the topic and as a discipline mechanism. They read and comment on the instructions for the activities to be done by the students. They monitor and review the activities, clarify doubts, make observations, give a grade, and finally, open up space for socialization. Incomplete activities are assigned as homework and then checked and graded the next day. In this regard, since 1960 other investigations have identified similar traits and characteristics in the teaching of Spanish and propose progress toward teaching that privileges communicative action.